Relationships between neighbourhood characteristics and current STI status among HIV-infected and HIV-uninfected women living in the Southern USA: a cross-sectional multilevel analysis. (7th March 2017) - Haley, Danielle F; Kramer, Michael R; Adimora, Adaora A; Haardörfer, Regine; Wingood, Gina M; Ludema, Christina; Rubtsova, Anna; Hickson, DeMarc A; Ross, Zev; Golub, Elizabeth; Bolivar, Hector; Cooper, Hannah LF
Abstract : Objectives: Neighbourhood characteristics (eg, high poverty rates) are associated with STIs among HIV-uninfected women in the USA. However, no multilevel analyses investigating the associations between neighbourhood exposures and STIs have explored these relationships among women living with HIV infection. The objectives of this study were to: (1) examine relationships between neighbourhood characteristics and current STI status and (2) investigate whether the magnitudes and directions of these relationships varied by HIV status in a predominantly HIV-infected cohort of women living in the Southern USA. Methods: This cross-sectional multilevel analysis tests relationships between census tract characteristics and current STI status using data from 737 women enrolled at the Women's Interagency HIV Study's southern sites (530 HIV-infected and 207 HIV-uninfected women). Administrative data (eg, US Census) described the census tract-level social disorder (eg, violent crime rate) and social disadvantage (eg, alcohol outlet density) where women lived. Participant-level data were gathered via survey. Testing positive for a current STI was defined as a laboratory-confirmed diagnosis of chlamydia, gonorrhoea, trichomoniasis or syphilis. Hierarchical generalised linear models were used to determine relationships between tract-level characteristics and current STI status, and to test whether these relationships varied by HIV status. Results: Eleven per cent of participants tested positive for at least one current STI. Greater tract-level social disorder (OR=1.34, 95% CI 0.99 to 1.87) and social disadvantage (OR=1.34, 95% CI 0.96 to 1.86) were associated with having a current STI. There was no evidence of additive or multiplicative interaction between tract-level characteristics and HIV status. Conclusions: Findings suggest that neighbourhood characteristics may be associated with current STIs among women living in the South, and that relationships do not vary by HIV status. Future research should establish the temporality of these relationships and explore pathways through which neighbourhoods create vulnerability to STIs. Trial registration number: NCT00000797 ; results.